Pemenuhan Restitusi Bagi Anak Korban Tindak Pidana Penganiayaan Berat Ditinjau Melalui Perspektif Viktimologi - Salsabila Oktaria Miraj; Annisa Marsya Nabila; Azka Rinjani; Farrel Augusto Pandelaki; Yunita Sari; Engely Pakpahan; Yuriko Kartika Puspita Sari (Jurnal Hukum dan Sosial Politik, 2024)
Restitution for child victims of serious criminal abuse is a human right guaranteed under the legislation. Indonesia Child Protection Law explicitly contains provisions regarding special protection for children who are victims of physical violence, established through several measures such as treatment and rehabilitation, psychosocial assistance as well as providing protection and assistance in every judicial process. In line with that, the victimology perspective developed in Indonesia's criminal law system also recognizes the vulnerable position of victims in the law enforcement process, thus requiring further action in the form of restitution for criminal victimization. However, in its implementation, inconsistencies in law application by law enforcers and societal factors often hinder the fulfillment of holistic restitution, which creates injustice for child victims whose rights are only partially fulfilled. Therefore, this research aims to examine the fulfillment of restitution for child victims of serious criminal abuse through the victimology perspective. This study employs a normative juridical methodology with a statutory approach and study case on South Jakarta District Court Decision number 297/Pid.B/2023/PN Jkt.Sel.. The data used in this study is secondary data and analyzed descriptively to provide a concise overview following the progressivity of children's rights protection who are victims of serious criminal abuse under Indonesian law. The findings of this study convey that the implementation of legal protection for child victims of serious criminal offense in South Jakarta District Court Decision number 297/Pid.B/2023/PN Jkt.Sel. by law enforcers has not been fully maximized and complies with the related laws as the main legal basis for the fulfillment of the right to restitution.